Survey of DAOA Gene Polymorphism in Schizophrenic Patients in Iran - Shadi Haghighat; Rasoul Zahmatkesh Roodsari; Reza Ranjbar (Majallah-i dānishgāh-i ̒ulūm-i pizishkī-i Arāk, 2017)
Abstract Background: Schizophrenia is a common mentaly disorder with high heritability and variable phenotype that they are placed in bipolar nervous disease family. Different genes are associated with this disease that among of them, DAOA gene plays a significant role. DAOA gene is located in the long arm of chromosome 13 and produces a protein called D-amino acid oxidase which is N - metyle D– aspartate (NMDA) receptor activator in the brain. The aim of this study was to investigate the association between DAOA gene polymorphisms and the risk of schizophrenia in Iranian population. Materials and Methods: In this study, 100 patients with schizophrenia and 100 normal people as a control group were investigated. After genomic DNA extraction from blood samples, allele and genotype frequencies in patients and control group were determined by PCR-RFLP method. Data analysis was performed with Med Calc (ver 12) software. Results: Frequency of GG, GA, AA genotypes in patients group was 18%, 42%, 40% and in normal group was 14%, 45%, and 41%, respectively. Statistical analysis revealed that there is a significant relationship between DAOA gene polymorphism with schizophrenia disease in the people under the age of 40. Conclusion: According to the results of this study, the DAOA gene has significant association with schizophrenia in the Iranian population.